Improv as cognitive activity - Krueger, Kristin R.; Winer, Jeffrey P.; Lattimore, Daniel C.; Beck, Todd; Dennis, Kyle; Carswell, Cameron; Saper, Clifton; Hainselin, Mathieu (Frontiers in Aging Neuroscience, 2025)
BackgroundEngaging in regular cognitive activity has been associated with cognitive function, yet the field of aging research has limited choices of cognitive activity programs to implement in clinical trials. As the field of aging research works to operationalize healthy habits, the potential role of improvisational theater (improv) to improve the lives of older adults has emerged. Given the limitations of existing cognitive training programs and the promise of improv, we sought to establish the feasibility of creating a cognitive training program based on improv exercises.MethodsWe engaged 13 neuropsychologists and trainees in 15 improv exercises and asked them to rate the extent to which each exercise engaged or required one of 20 distinct cognitive abilities or cognitive subdomains. We then examined the mean ratings of the highest and the lowest rated subdomains to provide evidence that each exercise could be mapped onto different cognitive subdomains, thereby providing evidence of concept.ResultsOur results demonstrated that these informed participants deemed the improv exercises as engaging cognitive processes. We found consensus among raters via higher-than-average means for specific abilities across the 15 exercises. Ratings from participants were broadly consistent with the pre-study groupings of the authors.DiscussionOur study provides the initial steps of establishing construct validity of improv exercises as a meaningful form of cognitive activity. This set of exercises can be examined as a cognitive training program in future clinical trials in order to determine if it has a significant influence on the cognitive function of older adults.